Improved Nutrient Management Practices for Enhancing Productivity and Profitability of Wheat under Mid-Indo-Gangetic Plains of India - Hanuman Prasad Parewa; Janardan Yadav; Vijay Singh Meena; Deepranjan Sarkar; Sunita Kumari Meena; Amitava Rakshit; Rahul Datta (Agriculture, 2022)
Two-year field experiments were conducted to study the effect of different levels of inorganic fertilizers, farmyard manure (FYM), and bio-inoculants on wheat productivity and profitability. Results specified that judicious application of inorganic fertilizers, FYM, and bio-inoculants significantly increased the productivity and profitability of wheat. Data suggested that the aggregate levels of fertilizer up to 100% NPK ha−1 resulted in significant increases in all growth attributes, grain yield (+206%), straw yield (+177%), and harvest index (+7%) as compared to control. Meanwhile, plots with the application of 10 t ha−1 FYM significantly (p < 0.05) increased grain yield (+26%) and straw yield (+22%) as compared to the control. Similarly, significant enhancement in grain and straw yields was observed with the application of PGPR + VAM over no-inoculation. Results showed that the significantly higher grain and straw yield attained by application of 75% NPK fertilizer + 10 t ha−1 FYM was at par with the application of 100% NPK fertilizer alone. Further, net returns (profitability) and B:C ratio (2.37) were significantly higher with fertilization with 75% NPK + 10 t ha−1 FYM along with PGPR + VAM as compared to 100% NPK alone. Overall, it can be concluded that the combination of 75% NPK and 10 t ha−1 FYM along with PGPR + VAM represented the optimum for net return and B:C ratio and reduced (25%) dose of NPK as compared to the rest of the treatment combinations.